Pattern of Primary Thyroid Malignancy in a Tertiary Care Hospital - Islam, Mohammad Asraful; Islam, Rashedul; Talukder, Debnath; Sayeed, AHM Noor E As; Rumi, SK Nurul Fattah; Choudhury, A Allam; Fakir, Md Abu Yousuf; Sitan, Kazi Noor (Journal of Dhaka Medical College, 2020)
Background: Among the endocrine malignancies thyroid cancer is the most common. It constitutes a heterogeneous group of malignancies ranking it as the fifth most common cancer worldwide. On health as well as health system it has severe implication. Thyroid cancer incidence is rising most rapidly worldwide. Different thyroid malignancy requires different management strategy. Proper addressing and prompt management of different thyroid malignancies can lessen the suffering. Objective: The study aimed to evaluate the pattern of primary thyroid malignancy in a tertiary care hospital. Methods: The study was a hospital based descriptive cross sectional study and was conducted in Dhaka Medical College Hospital, Dhaka for one-year period following approval of this protocol. Patients suffering from primary thyroid carcinoma admitted in or attending the outpatient department (OPD) in the department of Otolaryngology and Head-Neck Surgery was approached for inclusion in the study. Written informed consent was taken from the subject and ethical issues were ensured. A total of 50 individual suffering from primary thyroid carcinoma calculated by sample size formula was selected by inclusion and exclusion criteria and data was collected by interview using a semi-structured questionnaire and by personal document analysis. Collected data was analyzed by the SPSS 20 for windows. This study reflects the pattern of primary thyroid malignancy in a tertiary care hospital in Bangladesh. Results: Mean age of the participants was 32.7 years with SD ± 13.8 years, Minimum age was 17 years and maximum age was 70 years. Majority of the patients (46%) were in the age group of 31- 40 years. Among the participants, 70% were female and 30% were male. The majority of the patients belong to Dhaka and Rangpur divisions (26% & 22% respectively) of which maximum patients were from rural area (70%). By occupation, maximum (22%) of the study subjects were businessman, maximum study subjects were below SSC (24%) and maximum patients (42%) had relatively low income per month. Half of the participants had habit of tobacco. All patients (100%) had presented with palpable thyroid swelling. Among the total participants 54% had lymphadenopathy, 10% had dysphagia, 4% had hoarseness of voice and 4% had lumpiness in throat. Only 2% of patients had the symptom of dyspnoea. No palpable lymph nodes were found in 46% followed by Single node lymphadenopathy 26%, multiple nodules in one side in 18%, bilateral lymphadenopathy 8% and 20% participants had Central compartment lymphadenopathy. USG findings of thyroid revealed Single solid nodule in 22.0%, Single cystic nodule in 16.0%, multiple mixed (solid + cystic) nodules in 62.0% cases. FNAC findings revealed Anaplastic carcinoma in 2.0%, Follicular neoplasm in 16.0% and Follicular variant of papillary carcinoma in 8.0%. Papillary carcinoma found in maximum 70.0% cases. No lymphoma found whereas medullary carcinoma found in 4.0% cases. Histopathological findings confirmed Anaplastic carcinoma in 4.0%, Follicular carcinoma in 16.0%, Follicular variant of papillary carcinoma in 8.0% and Papillary carcinoma 68.0% cases. By histopathological examination no lymphoma found whereas medullary carcinoma found in 4.0% cases. Only 24% participants had hypertension and 76% had DM as co-morbid diseases. Distant metastasis of carcinoma was not present in any of the participants. Conclusion: In this study, middle age group and female sex prevalent thyroid cancer. Geographical distribution also has an important role. Business, low educational level, low socioeconomic status and tobacco smoking are found the most important risk factors. Histopathologically papillary carcinoma was predominant followed by follicular carcinoma, follicular variant of papillary carcinoma, anaplastic carcinoma and medullary carcinoma. No lymphoma found. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 161-174